The nuclear infrared emission of low-luminosity AGN - Mason, R; Lopez-Rodriguez, E; Packham, C; Alonso-Herrero, A; Levenson, N; Radomski, J; Almeida, C; Colina, L; Elitzur, M; Arextaga, I; Roche, P; Oi, N (2012)
We have obtained high-resolution mid-infrared (MIR) imaging, nuclear spectral energy distributions (SEDs) and archival Spitzer spectra for 22 low-luminosity active galactic nuclei (LLAGN; L bol < 5 × 10 42 erg s -1). Infrared (IR) observations may advance our understanding of the accretion ows in LLAGN, the fate of the obscuring torus at low accretion rates, and, perhaps, the star formation histories of these objects. However, while comprehensively studied in higher-luminosity Seyferts and quasars, the nuclear IR properties of LLAGN have not yet been well-determined. In these proceedings we summarise the results for the LLAGN at the relatively high-luminosity, high-Eddington ratio end of the sample. Strong, compact nuclear sources are visible in the MIR images of these objects, with luminosities consistent with or slightly in execss of that predicted by the standard MIR/X-ray relation. Their broadband nuclear SEDs are diverse; some resemble typical Seyfert nuclei, while others possess less of a well-defined MIR "dust bump". Strong silicate emission is present in many of these objects. We speculate that this, together with high ratios of silicate strength to hydrogen column density, could suggest optically thin dust and low dust-to-gas ratios, in accordance with model predictions that LLAGN do not host a Seyfert-like obscuring torus.